IoT Based Smart Water-quality Monitoring System - Chanthamenavong, Senglathsamy; Sisaykeo, Phonepaserth; Bounnady, Khampheth; Kanthavong, Somphone; Phoummavong, Phonepadith; Sisaat, Khamphao (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This article is made to design and create a device to measure water quality in real time with Internet of Things (IoT) technology. While also developing Database System for Web Application and Mobile Application that allow for water quality information access through Smart Phones, Computers and Tablets to make people access water quality information more easily, quickly, real-time, and decrease time and expenses to access water quality information. In our system, there are two main parts: Hardware, which manages hardware in our system such as Node MCU ESP32, PH (Potential of Hydrogen) sensor, EC (Electro Conductivity) sensor, DO (Dissolved Oxygen) sensor. Software, which manages information transferred from the hardware to save in the Database, and simultaneously shows the water quality information on Web Application and Mobile Application. Our Web Application and Mobile Application unique function is that it can locate the place that we install our devices to measure water quality. It also tells the PH, EC and DO to compare water quality in that place. pH is a principal factor in water quality control to make it suitable for the growth of living things. Ec is used to tell the purity of the place. DO is used to tell the property of the water. Our users can also download the PH, DO and EC information to use in their research as well.